Laptopia: The Spatial Poetics of Networked Laptop Performance. - Reddell, Trace (Contemporary Music Review, 2003)
Networked laptop performances prompt the articulation of new spatial poetics incorporating distributed modes of production, collaboration and reception. This article first tracks production in terms of Internet sampling: the browser-based DJ mixes of em.chia and the dj rabbi collective; direct file download and manipulation in my own work; networked curation projects of Atau Tanaka; and automated web-trawling programs like Freeman and Skeet's <earshot> and Traub's "Bits&Pieces". The article subsequently explores collaborative possibilities in interactive streams and multi-directional remixes, such as Brian Kane's "8-Track"; the cross-Atlantic laptop jam session of monolake (Berlin) and deadbeat (Montreal) at Mutek 2002; and [The User]'s Silophone. These performers fitter the concept of spatial poetics through traditions of broadcast technologies and telephony. Finally, the article raises the political implications of blurred production, performance and distribution boundaries in terms of networked laptops and mobile PA-systems, concentrating on the OpenAir Radiotopia project (Ars Electronica 2002) as a site of liberatory improvisational transmission.